2014
DOI: 10.1177/2051570714540553
|View full text |Cite
|
Sign up to set email alerts
|

Recycling household waste: A classification of the logistics used by consumers

Abstract: This research classifies the logistics used by consumers when recycling their household waste. Through an analysis of 20 waste recyclers, we identify three types of logistics depending on the characteristics of the recycling context and the desired relationship to waste: stockpiling, just-in-time and pooling. Contributing to the field of consumer logistics, our research shows that for the consumer recycling is not just a question of motivation and context, but also of logistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…This study also enriches the literature on household recycling that draws on the theory of planned behavior; it introduces demographic (age) and psychosociological variables (generativity) and resources (knowledge and available time), thereby establishing a link with the study of recycling through the question of the logistics needed for this activity (Monnot et al, ). Whereas those authors showed that the chosen recycling strategies depend on one's resources, our research reveals the link between individual determinants and such resources.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This study also enriches the literature on household recycling that draws on the theory of planned behavior; it introduces demographic (age) and psychosociological variables (generativity) and resources (knowledge and available time), thereby establishing a link with the study of recycling through the question of the logistics needed for this activity (Monnot et al, ). Whereas those authors showed that the chosen recycling strategies depend on one's resources, our research reveals the link between individual determinants and such resources.…”
Section: Discussionmentioning
confidence: 81%
“…These variables relate to diverse factors: psychological variables such as locus of control (McCarty & Shrum, ), demographic variables such as gender (Stern, Dietz, & Kalof, ), and social factors such as collectivism (Kim & Choi, ). Specifically, in relation to household recycling behaviors, Miafodzyeva and Brandt () and later Monnot, Reniou, and Rouquet () identified three major categories of individual determinants: demographic characteristics (age, income, level of education, and gender), internal dispositions (attitudes and values), and external motivations such as social norms, financial incentives, and available information. In addition to these variables, the waste collection system has also been identified as a key determinant of waste‐sorting behavior (Dahlén, Vukicevic, Meijer & Lagerkvista, ; Davies, Foxall, & Pallister, ).…”
Section: Age: a Variable Often Used To Study Recycling Behavior But Wmentioning
confidence: 99%
“…, ; Monnot et al. ) points out that to meet their daily consumption needs, individuals already perform logistics activities using their own assets. Recent studies in consumer logistics (Bahn et al.…”
Section: The Crowd a New Player In The Co‐creation Of Logistics Valuementioning
confidence: 99%
“…In fact, the only stream of research in logistics (Granzin and Bahn 1989;Granzin et al 1997Granzin et al , 2005. This emerging approach (Teller et al 2006(Teller et al , 2012Monnot et al 2014) points out that to meet their daily consumption needs, individuals already perform logistics activities using their own assets. Recent studies in consumer logistics (Bahn et al 2015) build on the service-dominant logic framework developed in the marketing field by Lusch (2004, 2008).…”
Section: The Crowd a New Player In The Co-creation Of Logistics Valuementioning
confidence: 99%
“…Thus, Woodall (2003) considers the potential cost of getting rid of the object. The logistics involved in the processing of residues (Monnot et al, 2014) can be interpreted in terms of non-monetary costs (time, effort), as well as psychological and relational costs related to the potential deliberation around the disposition of objects. Thompson (1979) and Parsons (2008) consider that the discarded object has no value.…”
Section: Prv and The Destinies Of Replaced Objectsmentioning
confidence: 99%